Chediak higashi syndrome: A case report of rare anomaly (Indian Journal of Case Reports, 2019)
Chediak Higashi syndrome (CHS) is a rare autosomal recessive immunodeficiency disorder that arises due to the mutation of a trafficking protein which leads to a decrease in phagocytosis. This results in frequent pyogenic infections, albinism, and peripheral neuropathy. Infections in these patients tend to be very serious and life-threatening. CHS is caused by mutations in a gene LYST on chromosome 1. Here, we report the case of CHS in a 4-year-old boy who presented to us with recurrent fever, splenomegaly, and hypopigmentation. This case is being presented due to its rarity and presentation of pancytopenia without hemophagocytosis.